APPLICATION OF ADJOINT EFFECTS IN THE TRAINING PROCESS OF VOLLEYBALL PLAYERS - Vladimir Magin; Mikhail Denisov (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the results of the research on introduction of the author's method of adjoint effects application into the training process ofskilled volleyball players. The efficiency of its application in the training process was approved by significantly elevated level of special preparedness of volleyball players. This technique is of pedagogical value for sports science and training of high-class athletes.